GAYA HIDUP PENDERITA HIPERTENSI PADA LANSIA DI WIALAYAH KERJA PUSKESMAS SABANG KECAMATAN DAMPELAS KABUPATEN DONGGALA - Niswa Salamung; Diah Fitri Purwaningsih (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2022)
Background: Hypertension is an increase in blood pressure in the arterial walls with a systolic of around 140 mmHg or more and a diastolic of 90 mmHg or more. Hypertension is caused by an unhealthy lifestyle, such as: high fat and salt foods, lack of physical activity, stress, and smoking. Hypertension occurs with increasing age which causes blood pressure in the elderly to increase because the arterial walls are thickened and result in a buildup of collagen substances in the muscle layer, causing the blood vessels to gradually narrow and become stiff. This study aims to identify the lifestyle of patients with hypertension in the elderly. Methods: This study used descriptive. The study population was 385 people and a sample of 39 people with the inclusion criteria of the elderly suffering from hypertension in the work area of the Sabang Health Center, the elderly who signed the informed consent and were willing to be respondents. Exclusion criteria for respondents who are sick. The sampling technique is probability sampling using the Simple Random Sampling method. Results: The results showed that the type of good food was 7.7%, the type of food was sufficient as much as 66.7%, the type of food was less as much as 25.6. Moderate exercise habits as much as 53.8%, less exercise habits as much as 46.2%. The smoking habit of 39 respondents there were 19 people who smoked, 31.6% light smokers, 63.2% moderate smokers and 5.3% heavy smokers. Conclusion: The type of food consumed by hypertension sufferers in the elderly is sufficient, exercise habits carried out by patients with hypertension in the elderly are in the sufficient category, and the smoking habits of patients with hypertension in the elderly are in the category of moderate smokers.